Risk Management of Carbon Steel Piping in Sweet Environment Multiphase Fluid Production - Tiggor, Triadhi Panthun; Riastuti, Rini (UI Scholars Hub, 2022)
As well reserved depleted and limited, it is necessary to lower the capital expenditure so that lifting SZ reservoir be more profitable. This article first contextualizes the effort done to increase the hydrocarbon lifting in a mature field. Despite the importance to sustain the production, and massive studies done to quantify the associate risk, no structured methodology proposed to manage the risk in respect to optimize the production expenditure by selection of carbon steel as alternative for corrosion resistance material piping. Hence, this article proposed a framework to support the decision-making process to operate in safely manner. Real case study proposed and evaluated shown 6.72-millimetre metal loss due to SEC and CO2 corrosion is expected to occur within 5 years’ design life. Hence, carbon steel pipe is allowed considering the risk mitigation define are provided and continuously monitored. Results shows the proposed framework increase the confidence level in putting the assessment results into proper decision-making process whilst improving the integrity management system.